Interculturality: Aspects that Impact the Foreign Language Learning of the Future FL Teachers at UIS (2024)
This study investigates the impact of interculturality on the foreign language learning experiences of future teachers at UIS. Focused on the first, fifth, and tenth semesters in 2023-2, our analysis, rooted in Dietz's (2012) framework, explores student perceptions through surveys, focus group interviews, and sharing circles. Findings reveal dynamic influences of interculturality on learning processes, evolving with semesters. The study provides information about the necessity of integrating intercultural considerations into language programs for a more inclusive and effective educational experience. In conclusion, embracing interculturality is not only a theoretical concept but a crucial element for optimizing the foreign language learning journey. This research contributes insights for educators and institutions seeking to enhance language programs through a nuanced understanding of intercultural dynamics.